2022
DOI: 10.1186/s12864-022-08734-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the cucumber PP2C gene family

Abstract: Background Type 2C protein phosphatase (PP2C) is a negative regulator of ABA signaling pathway, which plays important roles in stress signal transduction in plants. However, little research on the PP2C genes family of cucumber (Cucumis sativus L.), as an important economic vegetable, has been conducted. Results This study conducted a genome-wide investigation of the CsPP2C gene family. Through bioinformatics analysis, 56 CsPP2C genes were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 76 publications
14
26
0
Order By: Relevance
“…Both FvPP2C and FaPP2C were expressed mostly in the nucleus, cytoplasm, and chloroplast ( Supplementary Tables S1 and S2 ). Similar results were found in the cucumber study [ 52 ]. Therefore, we speculated that the PP2C protein was involved in respiration, photosynthesis, growth, and development of strawberry.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both FvPP2C and FaPP2C were expressed mostly in the nucleus, cytoplasm, and chloroplast ( Supplementary Tables S1 and S2 ). Similar results were found in the cucumber study [ 52 ]. Therefore, we speculated that the PP2C protein was involved in respiration, photosynthesis, growth, and development of strawberry.…”
Section: Discussionsupporting
confidence: 91%
“…Gene replication involves fragment replication, tandem replication, and genome replication, as above-mentioned, and fragment replication is more conducive for maintaining gene function than tandem replication [ 55 ]. It was found that there was fragment replication of the PP2C gene in both woodland and pineapple strawberries ( Figure 3 A,B), and similar results were found in A. thaliana [ 29 ], cucumber [ 52 ], and paper mulberry [ 53 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To elucidate further the phylogenetic evolutionary relationships and structural characteristics of bayberry AP2/ERF genes, we conducted an analysis of their exon-intron gene structure and conserved motifs [44]. The structural domains show that each gene has at least one AP2 structural domain.…”
Section: Gene Structure and Conserved Motif Analysis Of The Bayberry ...mentioning
confidence: 99%
“…S. portulacastrum, as a halophyte, has different PP2C gene expression levels compared to the control plants. CsPP2C genes in different groups have different responses to different stressors (Zhang G. et al, 2022), and these results provide a reference for the study of PP2C under salt stress. Salt stress has been alleviated using GA 3 as a growth regulator, which has been utilized to accelerate the growth of wheat and rice (Forghani et al, 2018).…”
Section: Phytohormone In Sesuvium Portulacastrum Responses To High Sa...mentioning
confidence: 79%